2021
DOI: 10.4314/jpb.v18i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of traditional medicine among people of Jos South Local Government Area of Plateau State, Nigeria

Abstract: Studies and documentation on the current knowledge and practices of traditional medicine among African communities are lacking particularly in this era of modern health care expansion. This study aimed at assessing the knowledge, attitude and practice of traditional medicine in Jos South Local Government Area (LGA) of Plateau State, Nigeria. A systemic random sampling technique was employed for this study. A semi-structured open and closed ended questionnaire was used to collect data through house to house int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
2
9
2
Order By: Relevance
“…28 Dissimilar to the current study, a study conducted in Nigeria reported that many of the study participants (81.4%) used TM and the main reported reasons for using TM were lack of improvement on modern medicine (51.1%) and side effects experienced from modern medicine (13.5%). 29 Other study also reported perceived failure of modern medicines (31.73%), relatively high price of modern medicines (23.08%), social–cultural practices and/or herbal knowledge (20.19%), poor availability and affordability to medical facilities (19.23%), safety concerns about modern medicines (9.62%), and uncaring attitudes of service providers (6.73%) as reasons for using TM. 30 Our study revealed that 43.3% of ever TM users prepared the medicine on their own, while 24.7% of TM users obtained from TM practitioners and this disagrees with a study conducted in Gondar town, Ethiopia, in which 37.6% of TM users obtained their medicine from the practitioners (herbalists) and 29% of TM users from relatives.…”
Section: Discussionmentioning
confidence: 98%
“…28 Dissimilar to the current study, a study conducted in Nigeria reported that many of the study participants (81.4%) used TM and the main reported reasons for using TM were lack of improvement on modern medicine (51.1%) and side effects experienced from modern medicine (13.5%). 29 Other study also reported perceived failure of modern medicines (31.73%), relatively high price of modern medicines (23.08%), social–cultural practices and/or herbal knowledge (20.19%), poor availability and affordability to medical facilities (19.23%), safety concerns about modern medicines (9.62%), and uncaring attitudes of service providers (6.73%) as reasons for using TM. 30 Our study revealed that 43.3% of ever TM users prepared the medicine on their own, while 24.7% of TM users obtained from TM practitioners and this disagrees with a study conducted in Gondar town, Ethiopia, in which 37.6% of TM users obtained their medicine from the practitioners (herbalists) and 29% of TM users from relatives.…”
Section: Discussionmentioning
confidence: 98%
“…In many cases, the theory and application are quite different from those of conventional medicine, even though, both practices are aimed at healing and prevention of diseases. for instance, the historical use of many traditional medicine practices, including experience passed from generation to generation, has demonstrated the safety and efficacy of traditional medicine [1]. Over the years, the significance of traditional medicine have also been established by different types of traditional medicine practitioners include herbal healers, herbal sellers, bone setters, traditional birth attendance and diviners.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, the significance of traditional medicine have also been established by different types of traditional medicine practitioners include herbal healers, herbal sellers, bone setters, traditional birth attendance and diviners. In addition, the investigation of folk beliefs and knowledge of traditional healers has been reported a short cut to the isolation of pharmacologically active compound [1]. In fact, the use of medicinal herbs by local populations of various cultures has served as starting point for drug discovery and has led to the development of many drugs used in treatment of diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that the global market of traditional medicine is approximately US $83 billion annually. In 2012, 32 billion dollars were spent in the United States of America on dietary supplements, an amount expected to increase to 60 billion dollars in 2021 [2]. Human has been using herbal medicines since the inception of their life on earth [1,2,3,4].…”
mentioning
confidence: 99%
“…In 2012, 32 billion dollars were spent in the United States of America on dietary supplements, an amount expected to increase to 60 billion dollars in 2021 [2]. Human has been using herbal medicines since the inception of their life on earth [1,2,3,4]. Herbal medicines have been often used as rst aid even before a patient has access to healthcare facilities [1,3].…”
mentioning
confidence: 99%